A Study into Methodological Issues in Cross-Cultural Pragmatic Research - Malekzadeh, Shirin (Richtmann Publishing, 2012)
The methodological issues are one of the areas of pragmatics which have gained considerable attention recently. Thefoundation of basic instruments in speech act research can be placed in a two-polar continuum. At one end, there are theperception/comprehension methods and at the other end production methods are placed. Each level then has its own specificinstruments. As for the perception/comprehension methods, instruments such as rating, multiple choice, and interview tasks canbe utilized. In production methods, instruments such as discourse completion, closed role play, open role play, and observationof authentic discourse are placed (Kasper & Dahl, 1991). Furthermore, methods can be categorized according to anelicited/observational continuum. In the elicited end, methods such as rating, multiple choice, interview tasks, discoursecompletion, closed role play, and open role play are placed. In the observational end, observation of authentic discourse is used.This study is useful for those novice researchers who are interested in conducting pragmatic studies and may not be familiarwhich instrument they should use in particular situation.